Development of Pancasila Snakes and Ladders Game Media in Civics Learning for Elementary School Students - Hendra, Hendra; Ramadhan, Nuri; Hariati, Emy; Prayogi, Muhammad Fani (Institut Agama Islam Negeri Palopo, 2024)
This study aims to develop a snakes and ladders game media on the material of Pancasila symbols for students and to determine the feasibility of using the media, as well as to determine the level of practicality of the media through the responses of educators and students after using the snakes and ladders game media on the material of Pancasila symbols. The research method adapts the development model developed by Borg and Gall. This research uses six steps as follows: 1) potential problems, 2) data collection, 3) product design, 4) product validation, 5) product revision, and 6) product trial. The data collection techniques used are the validation of the material expert questionnaire and the media expert questionnaire to determine the level of media feasibility and the student response questionnaire to determine the level of media feasibility. The subject of research and development is class IV A students at SD Negeri 105345 Sidodadi Ramunia, Beringin District. The results of research and development obtained a design in the form of snakes and ladders game media to introduce Pancasila symbols in Civics learning for class IV A at SD Negeri 105345 Sidodadi Ramunia, Beringin District, which obtained a feasibility score of 77% by media experts and 80% by material experts. Based on the results of the description above, the products developed by researchers are feasible and practical to use as learning media.